COLD STRESS-INDUCED CALLOGENESIS FROM ISOLATED ANTHERS OF CATHARANTHUS ROSEUS (L.) G. DON - V.R. NARKHEDKAR; J. A. TIDKE; N. J. CHIKHALE; S. N. BHUSARI (International Journal of Pharma and Bio Sciences, 2016)
Androgenic haploid production is a key tool for the production of homozygous plants within a short duration. In present study, the effect of cold stress as a pretreatment on anther culture of Catharanthus roseus (L.) G.Don was taken under consideration for callus induction. Cold pretreatment of buds at 8°C for 10 days and subsequent incubation on MS media in the dark was found to be best i.e. 59.99 ± 3.33%, for calli production. 2, 4 - D as a potent inducer of calli was taken at 10 mgL-1 and BAP in 2 mgL-1, at a constant concentration, where the varying concentration of NAA at 0.5 mgL-1 was best suitable for callus production. Anther culture on Bioera anther culture teaching kit showed less potential for callus production at the same set of condition as compared to the optimized MS media.